Visuals in foreign language teaching - Zewary, Sayed Mustafa (Kansas State University, 2011)
This study investigates the effectiveness of visuals in the language classroom. Two types of visual aids commonly used in the language classroom, video and still pictures, are used to elicit narratives from L2 English speakers, and these narratives are subsequently compared. The data come from eleven international students from a university English Language Program, who voluntarily participated in two separate 15-minute interviews. In each interview session, they were shown either a series of pictures or a video, both depicting a story. Upon completion of the presentation of each visual, participants were asked a prompt question and their narration of the events portrayed in the visuals recorded. The narratives were transcribed and analyzed in order to test (1) if still pictures and video are equally effective in eliciting elaboration in the narratives, defined in this case, as the number of new referents introduced and the number of adjective and verb types produced; and (2) if exposure to still pictures and video elicit narrations of similar length. Both kinds of visuals stimulated learners to create narratives and elaborate on what had been shown in them. The video task elicited narratives roughly 10% longer than the picture task in regards to the raw number of words. When linguistic factors were compared, participants introduced new referents at comparable rates in both tasks while they employed 10% more verb types in the video task. Additionally, the series of still pictures prompted participants to employ a much higher number of adjective types. These observations suggest that a series of still pictures are an effective alternative for video for eliciting narratives. This study provides support for the use of still pictures as an equivalent to videos in situations where videos are less accessible in language classrooms (due to lack of technological access).
Keywords: Foreign language; Teaching; Visual aids; Video; Oral narrative; Linguistics; English as a Second Language (0441); Foreign Language Instruction (0444); Language, Modern (0291)